Expanding Yarrowia lipolytica’s metabolic potential for detoxification of cyanogenic glycosides in edible plants - Fidelis Azi; Zhiyu Li; Peng Xu (Communications Biology)
Abstract Cyanides are highly toxic chemicals in several edible plants that threaten food safety and human health. A phenotypically distinct Yarrowia lipolytica strain that efficiently detoxifies multiple cyanogenic glycosides from edible plants was constructed using a family 1 glycosyl-hydrolase (GH1). The strain displayed higher growth rates and metabolic activities when exposed to high concentrations of cyanides than the wild-type. It overexpressed genes that promoted the binding of molecular oxygen to the cytochrome iv complex. The engineered strain repressed fatty acid production to optimize energy production and activated the cyanide-resistant respiratory (AOX) pathway to circumvent HCN toxicity and maintain cellular homeostasis. It upregulated ribosome biogenesis, the sec-dependent protein export pathway, and the sulfur relay system to facilitate the production and transmembrane efflux of the secreted GH1 hydrolase. It efficiently degraded linamarin, amygdalin, prunasin, and dhurrin in food plants including cassava, germinated sorghum and Apricot seeds. The strain produced high phospholipids to support new membrane production and could be a cost-effective source of single-cell phospholipids. The findings demonstrate that the strain is a robust, sustainable, and potentially efficient strain that could be used for industrial bioconversion of plant materials containing glycosylated toxicants into safe foods and animal feeds.